MODELING OPTICAL INTENSITY MODULATORS BASED ON MACH-ZEHNDER INTERFEROMETER BY SOFTWARE TOOL OF MICROWAVE CIRCUITS CALCULATION NI AWR DESIGN ENVIRONMENT - М. Е. Belkin; V. V. Golovin; Yu. N. Tyschuk; S. A. Kudzh; A. S. Sigov (Российский технологический журнал, 2016)
At the design stage of radio-electronic means using microwave photonics units, the cosimulation capability in a single CAD tool for the elements of microwave and optical ranges is a vital issue, and it is important to retain the ability to complex nonlinear analysis of the circuits and systems under design. One of the most suitable solution of this complex problem is in using working on symbolic level CAD tool NI AWR Design Environment (AWRDE) from National Instruments, which has extensive built-in library of multi-parametric models for electronic and topological components, functional modules, or system units. Following it, in the paper we offer an upgraded nonlinear physical equivalent-circuit model of the double-sideband optical modulator, fully implemented based on AWRDE Schematic library elements. Developing the model, we proposed for the first time and initially studied by AWRDE a nonlinear physical model of the single-sideband electro-optical modulator, comprising three Mach-Zehnder interferometers. During the simulations, the static and dynamic characteristics of the models in large-signal operation mode are analyzed by transmitting Ku-band microwave signals. Carrying out experimental verification has confirmed the correctness of the developed models.